Meteorological mechanisms involved in dust emissions over West Africa - (:unkn) unknown (My University, 2008)
In the framework of the present research work, two new mechanisms for dust emissions and transport over the Sahel have been identified: 1- The first one is related to the monsoon nocturnal flow dynamics; high turbulent winds at the leading edge of the monsoon flow density-current like are at the origin of dust mobilization (Bou Karam et al., 2008). 2- The second one is associated with the cyclonic activity in the ITD region, new phenomena discovered also in the framework of the present research work, to be the response to: (a) The strong horizontal shear and low-level convergence existing along the ITD and (b) enhanced northeasterly winds associated with orographic blocking of cool air masses from the Mediterranean Sea (Bou Karam et al., 2009a). Beyond their role on dust emissions, the two identified mechanisms offer for the uplifted dust the potential to attend high altitudes to be made available for long range transport. In addition, the simulation of three mechanism involved on dust emissions over West Africa by the atmospheric model MesoNH has been examined. The model was able to reproduce very well the dust emissions associated with: Low level jets (Todd et al., 2009), Monsoon leading edge high turbulent winds (Bou Karam et al., 2009b) and Sahelian cyclones (Bou Karam et al., 2009a). Also, model results suggest that dust emissions in the ITD region during summer when the ITD is located over the hot spots of West Africa are in the same order of dust emissions from the Bodélé depression in winter time, recognized as the most important African dust source.
Keywords: African Research